Assessment Report on the Bakossi Elung and Niwong Districts, Kumba Division, Cameroons (Colonial Letters and the Contact of Knowledges, 1922)
This file contains colonial memoranda and assessment report on Bakossi Elung and Niwong Districts, Kumba Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies